185 Accelerated Staff Assistance Program (ASAP): An innovative central staffing support program for human subjects research - Abbey Fisher; Steven Negron-Candelario; Lauren Van Scoy (Journal of Clinical and Translational Science)
Objectives/Goals: The goal of the Accelerated Staff Assist Program (ASAP) is to help fill staffing gaps in clinical and translational research. The program offers centralized staff to fill short-term needs including project startup prior to hiring, project implementation, parental leave, and Spanish-language research support. Methods/Study Population: Promotion of ASAP in the first year was targeted to Penn State College of Medicine faculty to determine demand. Current outreach includes promotion to all Penn State campuses through PSCTSI’s newsletter, seminars, and presentations. Consultation intake data includes a project summary, staffing needs, and funding information. A project agreement, charter, and budget are drafted and agreed to by the principal investigator before work begins. Assessments occur at 6 and 12 months to assess satisfaction of the consultation process and quality of staff support, Net Promoter Score, and qualitative feedback about the program. Results/Anticipated Results: In its first year, ASAP conducted 26 consultations and supported 10 projects. Approximately 75% of staff effort has been recovered through agreements during the most recent 6 months. In anticipation of project delays, we found that booking FTE up to 115% results in a consistent recovery of 75% FTE. Consultee needs include short-term, partial effort support (76% of requests), project start-up (12%), staff leave (4%), and other (8%). ASAP staff tasks include participant recruitment and retention, data collection and analysis in English and Spanish, and community engagement for recruitment. Program assessments with research teams are ongoing; preliminary qualitative and quantitative data are unanimously positive. Discussion/Significance of Impact: The ASAP program has demonstrated fiscal success and sustainability in its first year. Hiring of a well-qualified, bilingual staff person allowed for quick onboarding and project support within one month of hire. ASAP enables CTSI to fulfill our mission by providing critical support for research teams to meet objectives and achieve equity goals.